FREE VIBRATION ANALYSIS OF COMPOSITE LAMINATED PLATES USING HOST 12 (Journal of Engineering, 2012)
This paper presents an application of a Higher Order Shear Deformation Theory (HOST 12) to problemof free vibration of simply supported symmetric and antisymmetric angle-ply composite laminated plates.The theoretical model HOST12 presented incorporates laminate deformations which account for the effectsof transverse shear deformation, transverse normal strain/stress and a nonlinear variation of in-planedisplacements with respect to the thickness coordinate – thus modeling the warping of transverse crosssections more accurately and eliminating the need for shear correction coefficients. Solutions are obtained inclosed-form using Navier’s technique by solving the eigenvalue equation. Plates with varying number oflayers, degrees of anisotropy and slenderness ratios are considered for analysis. The results compared withthose from exact analysis and various theories from references